Hubungan Kadar Gula Darah dengan Diabetes Distress pada Pasien Diabetes Melitus - Christine Handayani Siburian; Cahyan Tessalonika Gulo; Eka Nugraha V. Naibaho (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Diabetes Mellitus (DM) is a metabolic disorder caused by insufficient production of the hormone insulin from the pancreas. Blood sugar level is a large amount of sugar or glucose in the blood that needs to be maintained within a normal range so that the body is not damaged. Diabetes distress is the concern of a person with diabetes about the disease, support, emotional burden and access to care which are all part of the life of a diabetic patient. The study aims to determine the relationship between blood sugar levels and diabetes distress in patients with diabetes mellitus at Rumah Sakit Umum Imelda Pekerja Indonesia Medan. This study is a quantitative study with a cross sectional approach. The population in this study were patients with diabetes mellitus at Rumah Sakit Umum Imelda Pekerja Indonesia Medan. The number of samples of this study were 46 respondents and sampling with purposive sampling technique. The instruments used were blood sugar level values and the Diabetes distress scale questionnaire. Data analysis in this study using Spearmen Rho test. The results showed that there was a relationship between blood sugar levels and diabetes distress in patients with diabetes mellitus (p value 0.002). The recommendation is that nurses need to provide non-pharmacological measures to overcome stress in patients with diabetes mellitus.